A Note on the New International Accounting Standards Board (IASB) Pronouncement IAS No. 19 (R). (January 2013) - Bloom, Robert
The subject of defined pension plans is very much in the news, given the current low interest rate environment and the fact that life spans have been increasing over the years. As a result, employer liabilities have increased, creating funding issues. The International Accounting Standards Board has issued a new standard on this subject to improve the measurement of such pensions on the balance sheet and income statement along with footnote disclosure by companies offering such plans. This article analyzes this standard, emphasizing its reporting and disclosure requirements.